Phagocytosis of Necrotic Debris at Sites of Injury and Inflammation - Westman, Johannes; Grinstein, Sergio; Marques, Pedro Elias (Frontiers in Immunology, 2020)
Clearance of cellular debris is required to maintain the homeostasis of multicellular organisms. It is intrinsic to processes such as tissue growth and remodeling, regeneration and resolution of injury and inflammation. Most of the removal of effete and damaged cells is performed by macrophages and neutrophils through phagocytosis, a complex phenomenon involving ingestion and degradation of the disposable particles. The study of the clearance of cellular debris has been strongly biased towards the removal of apoptotic bodies; as a result, the mechanisms underlying the removal of necrotic cells have remained relatively unexplored. Here, we will review the incipient but growing knowledge of the phagocytosis of necrotic debris, from their recognition and engagement to their internalization and disposal. Critical insights into these events were gained recently through the development of new in vitro and in vivo models, along with advances in live-cell and intravital microscopy. This review addresses the classes of “find-me” and “eat-me” signals presented by necrotic cells and their cognate receptors in phagocytes, which in most cases differ from the extensively characterized counterparts in apoptotic cell engulfment. The roles of damage-associated molecular patterns, chemokines, lipid mediators, and complement components in recruiting and activating phagocytes are reviewed. Lastly, the physiological importance of necrotic cell removal is emphasized, highlighting the key role of impaired debris clearance in autoimmunity.